Romanian-French Contacts at the Level Of Military Decision-Makers - Nicolescu, Andrei (Technium Social Sciences Journal, 2023)
In 1932 and 1933 invitations to Generals Gamelin and Petin to visit Bucharest were declined on the basis of more or less objective reasons, this was not the case from 1934 onwards, when the frequency of such French visits to Bucharest increased. There was also a clear change in the level of representation, culminating in the visits of Generals Pétin, Mittelhauser, Georges, Gamelin and Weygand. Another significant moment for the development of the French-Romanian military relations was the presence in Bucharest of General Victor Pétin. It took place in a different context from that of General Gouraud's arrival, with different dimensions and connotations.The consequences of the visits, based primarily on the growing convergence of French and Romanian interests at that time, were felt. On the 8th of June, the Europe Sub-Directorate of the French Ministry of Foreign Affairs affirmed the need to accept Romanian arms requests by means of a commitment to supply on credit and with annual instalments. One of the arguments put forward was that: 'As a faithful ally, Romania, like Yugoslavia, is part of the Small Alliance and the Balkan Alliance, whose policy tends to be in line with the direction of action decidedly favourable to the preservation of the established order, cannot but receive the approval of the Government of the Republic.